SISTEM KAJI DUDUAK SEBAGAI STRATEGI PEMBELAJARAN MAHARAH AL-QIRA’AH DI MADRASAH BATANG KABUNG - Ansyah, Supriadi; Ritonga, Mahyudin; Alrasi, Fitri (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
This research aims to expose the system of Kaji Duduak as one of the strategies for learning qira'ah, specifically the aspects that will be exposed in this study are related to learning materials qira'ah, implementation methods and measures of use of the system Kaji Duduak as a strategy of learning qira'ah. The method of research used is qualitative with a phenomenological approach, data collection is done by observation, interviews and documentation. Data analysis techniques used classification, display and draw conclusions, to the validity of data use triangulation. The results of the study were: 1) learning materials qira'ah with a strategy kaji Duduak sourced from kitab kuning, 2) The implementation method more emphasis on qira'ah jahriyah, 3) measures used in teaching the maharah qira'ah with the strategy of Kaji Duduak: a) Students seated in the presence of ustadz, b) Teachers read the book that is listened to by students, c) Students are asked to restart the readings in turns , d) Reading material is analyzed using certain codes and distinctive mentions with Minang language, e) reading material translated based on i'rab.